A policy framework for analyzing multi-use pass pricing decisions. Issue 2 (3rd March 2016) - Crompton, John L.
Abstract : The multi-use pass is widely used by public sport and leisure agencies. Typically, it offers users a potential discount on price for a season or year. Decisions on pricing these passes often are reflexive and imitative, rather than thoughtful and explicitly analytical. This paper provides a policy framework composed of four dimensions that should be analyzed in multi-use pass pricing decisions. The first three are: encouragement of commitment; potential for leveraging more revenues from existing users; and adherence to the Benefit Principle. The analysis of these dimensions assumes the pricing goal is to maximize revenues. The fourth dimension, adherence to the Ability to Pay Principle, recognizes that maximizing revenues has to be reconciled with the obligation of agencies to be inclusive.